Direct and indirect effects of Holocene climate variations on catchment and lake processes of a treeline lake, SW China - Chen, Xu; McGowan, Suzanne; Xiao, Xiayun; Stevenson, Mark A.; Yang, Xiangdong; Li, Yanling; Zhang, Enlou (Elsevier, 2018)
Sedimentary records of inorganic elements and pigments over the last 12,000 years are used to assess major changes in limnological conditions of Tiancai Lake (a small treeline lake, SW China), in response to Holocene climate variations. Algal communities shifted from the dominance of cyanobacteria and cryptophytes in the early Holocene, towards siliceous algae in the mid-Holocene and chlorophytes in the late Holocene. Algae responded to a combination of climate-mediated vegetation and soil development associated with allochthonous inputs of dissolved nutrients and organic matter, and sediment infilling. Decreases in Al, Pb, Cu and Zn from the early Holocene probably resulted from soil podsolization and the sequestration of these elements within soils. Changes in Mn and Fe were likely linked to redox condition in catchment soils and water column. Synchronous peaks in Ti, Ba, Ca, Sr, Na, K and Mg, median grain size and magnetic susceptibility coincided with the troughs in the chemical index of alteration, indicating that episodic cold events enhanced upland bedrock erosion and transported unleached and coarse detritus into the lake. These cold events broadly correlate with Holocene ice-rafting events in the North Atlantic. Although the cold events altered the influx of minerogenic elements by regulating upland bedrock erosion, climate-mediated vegetation and soil development led to a muted impact on primary producers. Holocene algal community shifts were subtle, reflecting the relative abundance of P (derived from weathering) and N (derived from soils) throughout the record, with the most pronounced effects on the lake biota being benthic expansion which occurred in response to sediment infilling.